Development of a geospatial database for planning land protection measures against wind erosion - Moskalenko, A.; Andriianov, V. (Land Management, Cadastre and Land Monitoring, 2025)
This study describes the development of a structure that provides an opportunity to systematize and accumulate geospatial and attributive data. In the course of the research, a geospatial data base model was developed, which ensures the accumulation of data to solve the problem of spatio-temporal analysis and support the justification of land protection measures against wind erosion. The geospatial database model is developed using a UML class diagram that illustrates not only the main design components, but also details the attributes and their data types. The article structured an algorithm for analyzing geospatial data, structured and accumulated in a geospatial data base, to determine lands that may be threatened by wind erosion. The algorithm is presented through a functional model. The research developed a model of the knowledge base as a component of the geospatial database, which contains both standards and additional influencing factors that affect the increase or decrease of the risk of wind erosion. The work presents a geoimage of the studied territory with the selection of territories that may be subject to wind erosion in different seasons. The results of the work can be used in the process of planning land protection measures to protect against wind erosion. Key words: geospatial database, wind erosion, geoimages.